Penerapan Metode Six Sigma dan Failure Mode Effect Analysis dalam Pengendalian Kualitas Produk Sarung Tangan Golf di CV Cahaya Setia Mulia Abadi - Ahmad Luqmanul Farras; Widya Setiafindari (Politeknik Kampar, 2025)
CV Cahaya Setia Mulia Abadi is a manufacturing industry that produces sports gloves made of leather and synthetic materials. The golf glove product of the Brance brand studied from January 9-29, 2025 had a high defect rate of 1135 units so that improvements needed to be made to reduce defects in its production. Quality control is carried out through the Six Sigma approach using stages and a number of methods such as SIPOC, P Control Chart, Fishbone Diagram, and 5W + 1H. The purpose of this method is to identify the type of product defect, find out the cause of the defect, and formulate appropriate improvement efforts. FMEA analysis is also applied to identify potential failures based on the highest RPN value. At the define stage, 4 types of defects are known to be processed using the CTQ diagram, namely open stitches, holes, damaged variations, and asymmetrical. The next stage is measure which produces a CL value of 0.04668, UCL 0.051, and LCL 0.04262. The analysis of the analyze stage shows that the source of defects comes from human factors, machines, methods, materials and the environment. The potential causes of defects were further analyzed through FMEA with the highest RPN of 168, with the type of open stitch defect. In the improve stage, a proposal for corrective actions was prepared for all factors. In the control stage, efforts were made to ensure that corrective actions could be implemented consistently and effectively.